Real-time gated proton therapy: Introducing clinical workflow and failure modes and effects analysis (FMEA) - Wei Yang Calvin Koh; Hong Qi Tan; Kah Seng Lew; Wan Ting Alice Kor; Nur Atiqah Binte Samsuri; Jason Wei Siang Chan; Clifford Ghee Ann Chua; James Kuan Huei Lee; Andrew Wibawa; Zubin Master; Sung Yong Park (Technical Innovations & Patient Support in Radiation Oncology)
Introduction: Real-Time Gated Proton Therapy (RGPT) has been used in proton therapy to mitigate respiratory motion challenges. This study presents the first comprehensive description of the RGPT clinical workflow at the National Cancer Centre Singapore (NCCS) and introduces a novel Failure Modes and Effects Analysis (FMEA) for RGPT. Methods: We detail the workflow for prostate and liver/lung proton treatments. The FMEA, following AAPM TG-100 guidelines, evaluated potential failure modes based on occurrence, detectability, and severity. This comprehensive risk assessment approach allows for the establishment of robust Quality Assurance (QA) protocols, enhancing treatment safety and efficacy. The FMEA was performed by two disciplinary groups, namely the medical physicists and radiation therapists. Intraclass Correlation Coefficient (ICC) is used as the metric to assess the consistency of ratings among participants. Results: Since implementation, 15 patients (13 prostate, 2 liver) have been treated with RGPT. The study identified 96 potential failure modes, with 47 evaluated by two disciplines. Inter-rater concordance analysis revealed strong agreement within one group, while combined groups showed lower consistency, highlighting potential differences in risk perception between disciplines. Notably, severity ratings demonstrated better correlations among raters compared to other categories, suggesting a shared understanding of the potential impact of failures. Conclusion: This study provides valuable insights for institutions implementing RGPT, potentially enhancing treatment workflow, patient safety, and QA procedures. The detailed workflow description and FMEA results offer a foundation for standardizing RGPT practices and prioritizing risk mitigation strategies. Future research should focus on multi-institutional collaborations to further refine RGPT protocols and risk assessments.